ANALISIS EFISIENSI KETERSEDIAAN AIR BAKU DENGAN KONSEP SAVING RECYCLING PADA GEDUNG APARTMENT GRAND TAMAN MELATI 2 - Indra Hilmi Fauzan; Andi Tenrisuki Tenriajeng (Politeknik Negeri Jakarta, 2020)
It is the main and important element to be fulfilled, water becomes the primary need in all elements of life of living things so that they can continue to live life and all its activities. Besides that water is also in secondary needs as a means of transportation. Even water is also able to become a recreational facility so that water can also be said as a complement to tertiary needs. Water covers almost 71% of the Earth's surface. There are 1.4 trillion cubic kilometers (330 million miles) available on Earth. Viewed from the point of view of public health, the average volume of water requirements for each individual per day ranges from 150-200 liters or 35-40 gallons. The water requirements vary and depend on the climate, living standards and habits of the people. Reduced population of vacant land results in the availability of land to be reduced and limited. This makes the opportunity for hotel and apartment properties to increase. For some large cities, the presence of hotels and apartments is increasing every year, of course this will have an impact on the needs and availability of clean water that must be available every day. Because this research is very important to make an effort that is able to minimize the use of ground water by saving water and recycling water methods. The effort is able to be a solution to the efforts to create efficient use of ground water. Exactly this Water Management Infrastructure Engineering is carried out in the Grand Taman Melati Margonda Apartment 2. With a total unit reaching 939 units. Aspects that are the focus of the results of this study are aspects of quantity and cost.